(untitled) (Bioscience Journal, 2020)
This study aimed at evaluating the agronomical performance of ‘Pineapple’ sweet orange grafted on ten rootstocks, in 2011-2017 harvests, so as to recommend the best combinations to be commercially explored in citrus growing regions in Bahia and Sergipe states, Brazil. An experiment was installed to test ten rootstock for ’pineapple’ sweet orange: ’Santa Cruz’ Rangpur lime, ’Red Rough’ Lemon, ’Orlando’ Tangelo, ’Sunki Tropical’ Mandarin, ’Swingle’ citrumelo, the citrandarins ’Indio’ and ’Riverside’ and the hybrids HTR-051, LVKxLCR-010 and TSKxCTTR-002. The trial was installed in 2008 in the municipality of Umbauba in Sergipe. The experimental design was complete randomized blocks with four replications and two plants per plot. Plant spacing was 6 x 4 m which corresponds to 416 plants per hectare and the orchard was rainfed and followed conventional management. The following agronomical parameters were evaluated: vegetative growth, drought tolerance, yield and physico-chemical quality of fruits as well as the abundance of phytophagous mites. Both hybrids LVK x LCR – 010 and TSKC x CTTR-002 and the ‘Santa Cruz’ rangpur lime bestowed higher tolerance to the dry period on the ‘Pineapple’ orange tree, by comparison with higher water deficit susceptibility conferred by the ‘Orlando’ tangelo and the ‘Swingle’ citrumelo. Rootstocks HTR-051, ‘Riverside’ citrandarin, ‘Swingle’ citrumelo and TSKC x CTTR-02 induced plants to remain small and, thus, showed aptitude for culture densification. Cumulative yield of the ‘Pineapple’ orange was higher on rootstocks ‘Red Rough’ lemon and ‘Santa Cruz’ Rangpur lime, the hybrid LVK x LCR-010 and ‘Sunki Tropical’. Yield efficiency was not influenced by the rootstocks. Physico-chemical quality of fruits of ‘Pineapple’ orange is affected by the rootstocks and meets the requirements of juice industries. Regarding plant resistance, the rootstocks did not influence the population density of mites P. oleivora, E. banksi and T. mexicanus on ‘Pineapple’ oranges. Results show that both rootstocks ‘Red Rough’ lemon and ‘Santa Cruz’ rangpur lime conferred high regularity to ‘Pineapple’ orange trees in citrus growing regions in Bahia and Sergipe states.